Polyphenol Stability and Physical Characteristics of Sweetened Dried Cranberries - Kara Kovacev; Brianna Hughes; J. Scott Smith (Foods, 2020)
There is little research on how product matrix and processing affect phenolic compounds in sweetened dried cranberries over time. The objective of this research was to assess polyphenol content and stability in sweetened dried cranberries between product matrix types. This research assessed five commercially available sweetened dried cranberry matrices: (1) sliced apple juice infused, (2) whole apple juice infused, (3) sliced sucrose infused, (4) whole sucrose infused, and (5) sliced soluble corn fiber, glycerin, sucrose, and sucralose infused (three replicates/treatment). Proanthocyanidins, anthocyanins (HPLC), total phenolic content (Folin–Ciocalteu), water activity, moisture content, color, and texture were evaluated over 12 months at 21 °C. Data were analyzed by ANOVA (p < 0.05). Results demonstrate that sweetened dried cranberry polyphenols are unstable regardless of product matrix. More research is needed to determine optimal processing parameters for sweetened dried cranberries to maintain polyphenol stability as healthier food options for consumers.